Classroom note: Radioactivity half-lives considered as data. Issue 1 (1997) - Hutchinson, T. P.
Abstract : Half-lives of radioactive nuclides range over more than 20 orders of magnitude. It is striking that, nevertheless, statistical laws may be discovered in these numbers: a log-normal distribution provides a good description.